Correlation Analysis Between Physical–Chemical and Biological Conditions in the River and the Incidence of Diseases in the City of Piracicaba, Brazil - Alexander Ossanes de Souza; Deoclecio Jardim Amorim; Ernani Pinto (Toxics)
The Piracicaba River basin, in the State of São Paulo, Brazil, covers approximately 12,400 km2 and plays a crucial economic role in São Paulo’s agribusiness corridor. However, it faces recurrent episodes of pollution, impacting water quality and public health, especially in urban areas exposed to contamination. Despite this, few studies have investigated the ecological and epidemiological consequences of this environmental degradation. Therefore, this study analyzed the correlation between physicochemical and biological variables of the Piracicaba River and the incidence of diseases in the city of Piracicaba between January 2019 and September 2024. Data on hospital admissions for respiratory, neurological, and liver symptoms were used, as well as environmental and water quality information, such as dissolved oxygen, turbidity, conductivity, and the presence of cyanobacteria, obtained from public databases. The results showed seasonal patterns and long-term trends, highlighting the health risks associated with the river’s pollution. Parameters such as phosphorus, pH, cyanobacteria concentration and climatic factors (temperature and humidity) showed an influence on the occurrence of respiratory, digestive, and neurological diseases. The study reinforces the need for continuous monitoring of water quality and public policies to mitigate impacts on the population’s health.